ANALISIS KUALITATIF IMPLEMENTASI FUNGSI PENGAWASAN BADAN PERMUSYAWARATAN DESA DALAM MENINGKATKAN KINERJA PEMERINTAH DESA - Neli Yuliawati; Rachmat Rachmat; Zia Putria (PT. ABIG RIZKY PUBLISHER, 2025)
This study aims to analyze the implementation of the supervisory function of the Village Consultative Body (BPD) on the performance of the village government in Bojongpetir Village, Tanggeung District, Cianjur Regency. This research employs a qualitative approach with a descriptive method. Informants were selected using purposive sampling, including BPD members, the village head, village officials, and community leaders. Data collection techniques include observation, in-depth interviews, and documentation. Data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing, with validity ensured through triangulation. The results indicate that the supervisory function of the BPD has been implemented but not yet optimal. The BPD has conducted supervision on budget management and village program implementation; however, several obstacles remain, such as low member participation, limited resources, and weak coordination with the village government. Consequently, the performance of the village government in terms of transparency and accountability has not been fully achieved. Efforts made include improving the capacity of BPD members and strengthening coordination mechanisms. This study concludes that optimizing the role of the BPD is essential to achieve good village governance.